2000
DOI: 10.2307/177170
|View full text |Cite
|
Sign up to set email alerts
|

Bird-Ectoparasite Interactions, Nest Humidity, and Ectoparasite Community Structure

Abstract: Abstract. Host nests are the key habitat for ectoparasite species that live and reproduce within the nest material. Nest properties can influence host and parasite reproductive success, and therefore the outcome of host-parasite interactions, as well as the composition of parasite communities. Previous correlational results suggested that nest humidity may increase the negative effect of fleas on Great Tit (Parus major) reproductive success. Since the causality of the relationship was unknown, we simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 23 publications
4
42
1
Order By: Relevance
“…Several studies have focused on the effect of abiotic factors on the structure of ectoparasite communities (Krasnov et al 1997;Heeb et al 2000). Nest properties, such as humidity, influence the abundance of fleas in birds (Heeb et al 2000), whereas Krasnov et al (1997) showed the importance of host habitat on the abundance of fleas in rodents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on the effect of abiotic factors on the structure of ectoparasite communities (Krasnov et al 1997;Heeb et al 2000). Nest properties, such as humidity, influence the abundance of fleas in birds (Heeb et al 2000), whereas Krasnov et al (1997) showed the importance of host habitat on the abundance of fleas in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Nest properties, such as humidity, influence the abundance of fleas in birds (Heeb et al 2000), whereas Krasnov et al (1997) showed the importance of host habitat on the abundance of fleas in rodents. A positive effect of increasing host density on prevalence and abundance of two flea species was observed in the desert rodent Gerbillus dasyurus (Krasnov et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Blow Xy larvae develop into three successive larval stages before pupating (Bennett and Whitworth 1991). The tiny Wrst-stage larvae are particularly diYcult to detect so that our estimate of blow Xy infestation intensity only included the total number of second-stage larvae, third-stage larvae and pupae, following the protocols applied by Hurtrez-Boussès (1996) and Heeb et al (2000).…”
Section: Estimation Of Blow Xy Infestation Intensitymentioning
confidence: 99%
“…Although some ticks can respond to host cues and move towards the host over short distances (Barnard 1986;Heeb et al 2000;Milne 1950), they risk desiccation, predation and the uncertainty of locating their more mobile hosts (Hair and Bowman 1986;Petney et al 1983). Instead, many ticks adopt a sit-and-wait strategy in favourable microclimates and rely on the behaviour of host individuals to make contact.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, many ticks adopt a sit-and-wait strategy in favourable microclimates and rely on the behaviour of host individuals to make contact. For instance bird ectoparasites in nests rely on host individuals reusing the nest (Brown and Bomberger Brown 1986;Heeb et al 2000), and mammal ectoparasites that detach in burrows (Butler and Roper 1996;Roper et al 2002) have a good chance that the same individual may reuse the burrow, or a conspecific will share use of the burrow, making host contact highly probable.…”
Section: Introductionmentioning
confidence: 99%